Adverse Reactions to Iodinated Contrast Media - Bottinor, Wendy; Polkampally, Pritam; Jovin, Ion (International Journal of Angiology, 2013)
The use of iodinated contrast agents for angiography dates back to the 1920s. With over 75 million contrast-requiring procedures performed annually worldwide, it is important to understand the risk factors, pathogenesis, diagnosis, prevention, and treatment of adverse reactions caused by iodinated contrast media (ICM). As contrast media have evolved from ionic, high-osmolality to nonionic, low-osmolality formulations the risk of reactions has decreased over time; however, no pretreatment protocol has been shown to eliminate all repeat reactions. Clinical alertness and early recognition of adverse reactions is of paramount importance and key for appropriate management of these patients. In this article, we review the most recent literature regarding adverse reactions to ICM and provide an insight into the pathogenesis, clinical presentation, pretreatment, and management of contrast-related reactions.
Keywords: iodinated contrast media; contrast allergy; contrast prophylaxis; contrast nephropathy